A Miniaturized Reconfigurable CRLH Leaky-Wave Antenna Using Complementary Split-Ring Resonators. (7th March 2018) - Patron, Damiano; Liu, Yuqiao; Dandekar, Kapil R.
Abstract : Composite Right-/Left-Handed (CRLH) Leaky-Wave Antennas (LWAs) are a class of radiating elements characterized by an electronically steerable radiation pattern. The design is comprised of a cascade of CRLH unit cells populated with varactor diodes. By varying the voltage across the varactor diodes, the antenna can steer its directional beam from broadside to backward and forward end-fire directions. In this paper, we discuss the design and experimental analysis of a miniaturized CRLH Leaky-Wave Antenna for the 2.4 GHz WiFi band. The miniaturization is achieved by etching Complementary Split-Ring Resonator (CSRR) underneath each CRLH unit cell. As opposed to the conventional LWA designs, we take advantage of a LWA layout that does not require thin interdigital capacitors; thus we significantly reduce the PCB manufacturing constraints required to achieve size reduction. The experimental results were compared with a nonminiaturized prototype in order to evaluate the differences in impedance and radiation characteristics. The proposed antenna is a significant achievement because it will enable CRLH LWAs to be a viable technology not only for wireless access points, but also potentially for mobile devices.